Constitutive programmed death ligand 1 expression protects gastric G‐cells from Helicobacter pylori–induced inflammation. Issue 5 (28th July 2022) - Mommersteeg, Michiel C.; Yu, Bing Ting; van den Bosch, Thierry P. P.; von der Thüsen, Johan H.; Kuipers, Ernst J.; Doukas, Michael; Spaander, Manon C. W.; Peppelenbosch, Maikel P.; Fuhler, Gwenny M.
Abstract: Introduction: Gastric intestinal metaplasia (GIM) is a premalignant lesion, highly associated with Helicobacter pylori infection. Previous studies have shown that H. pylori is able to induce the expression of programmed death ligand 1 (PD‐L1), an inhibitory immune modulator, in gastric cells. Our aim was to investigate whether tissues from GIM patients may exploit PD‐L1 expression upon H. pylori infection to evade immunosurveillance. Methods: Immunohistochemistry was performed for PD‐L1 and enteroendocrine markers somatostatin and gastrin on samples derived from a cohort of patients with known GIM, both before and after H. pylori eradication. To determine the identity of any observed PD‐L1‐positive cells, we performed multiplex immunofluorescent staining and analysis of single‐cell sequencing data. Results: GIM tissue was rarely positive for PD‐L1. In normal glands from GIM patients, PD‐L1 was mainly expressed by gastrin‐positive G‐cells. While the D‐cell and G‐cell compartments were both diminished 2‐fold ( p = .015 and p = .01, respectively) during H. pylori infection in the normal antral tissue of GIM patients, they were restored 1 year after eradication. The total number of PD‐L1‐positive cells was not affected by H. pylori, but the percentage of PD‐L1‐positive G‐cells was 30% higher in infected subjects ( p = .011), suggesting that these cells are preferentially rescued from destruction. Conclusions: Antral G‐cells frequently express PD‐L1 during homeostasis. G‐cells seem to be protected from H. pylori ‐induced immune destruction by PD‐L1 expression. GIM itself does not express PD‐L1 and is unlikely to escape immunosurveillance via expression of PD‐L1.